Shoot tip grafting in kinnow to get virus-free plants - Kumar, Raj; Singh, A K; Kaul, M K (Indian Horticulture, 2019)
Introduction: The shoot tip grafting (STG) is most important technique for the development of disease-free planting material, especially for viruses. More than 90 per cent successes of grafts can be achieved by grafting kinnow on Carrizo Citrange rootstock. The STG can be commercially exploited for production of disease-free and healthy planting material in citrus.